Paediatric laryngotracheal Cases: Universiti Sains Malaysia Experience - Hamid, Suzina Sheikh Ab. (Universiti Sains Malaysia, 2009)
There are many inherent challenges in the evaluation and management of children with laryngotracheal disorders, and differ widely from one institution to another. The main challenges include access to suitable equipment, fully trained surgeon and, cooperation with the anaesthetist and paediatrician. During the past five years great advances have been made in managing paediatric airway cases in the Department of Otorhinolaryngology-Head & Neck Surgery at Universiti Sains Malaysia. The paediatric laryngotracheal cases undergoing microlaryngoscopy and bronchoscopy from 2004 to 2008 are presented. More than 80 cases have been reviewed. The most commonly presenting symptom was stridor. Other reasons for referral were laryngotracheal stenosis, foreign body inhalation, unresolved lung disease, failed extubation, examination prior to decannulation and hoarseness. Interventions were varied and tailored to each problem. The management include observation, medical treatment, closed (encdoscopic) techniques and open surgery.